2016
DOI: 10.1097/aln.0000000000001026
|View full text |Cite
|
Sign up to set email alerts
|

Classically Activated Macrophages Protect against Lipopolysaccharide-induced Acute Lung Injury by Expressing Amphiregulin in Mice

Abstract: Background Alveolar macrophages (AMs) activated into M1 phenotype are involved in the development of lipopolysaccharide-induced acute lung injury (ALI). However, whether AMs express amphiregulin and what roles amphiregulin plays in lipopolysaccharide-induced ALI remain poorly understood. Methods Acute lung injury was induced by intratracheal instillation of lipopolysaccharide in male C57BL/6 mice. Lung injury scores, level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…The data support a potential balance shift with the coexposure modeling towards interstitial disease because collagen deposition and tissue levels of extracellular matrix proteins (ie, hyaluronan and fibronectin) remained elevated or augmented in the setting of CIA + ODE despite decreased levels of the classic inflammatory mediators. AREG has been characterized as both protective and injurious in the progression of various lung diseases as it can promote proresolution effector cell function and epithelial repair processes, but overexpression can lead to fibrotic remodeling . Amphiregulin remained elevated with coexposure in the lung tissues, which is interpreted to be supportive of evidence towards interstitial disease.…”
Section: Discussionmentioning
confidence: 91%
“…The data support a potential balance shift with the coexposure modeling towards interstitial disease because collagen deposition and tissue levels of extracellular matrix proteins (ie, hyaluronan and fibronectin) remained elevated or augmented in the setting of CIA + ODE despite decreased levels of the classic inflammatory mediators. AREG has been characterized as both protective and injurious in the progression of various lung diseases as it can promote proresolution effector cell function and epithelial repair processes, but overexpression can lead to fibrotic remodeling . Amphiregulin remained elevated with coexposure in the lung tissues, which is interpreted to be supportive of evidence towards interstitial disease.…”
Section: Discussionmentioning
confidence: 91%
“…A direct function of amphiregulin in restoring lung function was initially demonstrated in influenza virus‐infected mice and patients with COPD and asthma have increased amphiregulin expression in their sputum and lungs . An increasing number of reports suggest that myeloid cells in the lung may also produce amphiregulin, and recently, it was demonstrated that proinflammatory AM produce high levels of amphiregulin during lipopolysaccharide‐induced lung injury to dampen inflammation . Similarly, in a bleomycin mouse lung injury model, amphiregulin generated from adoptively transferred AM promoted activation of fibroblast proliferation, motility, and indirectly, myofibroblast differentiation .…”
Section: Macrophages In Pulmonary Tissue Repairmentioning
confidence: 99%
“…; Xu et al. ). Prior studies have found that AREG promotes epithelial repair in LPS‐induced ALI and influenza infection, and in vitro studies have shown that it enhances regulatory T cell activity (Monticelli et al.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, administration of an antibody to neutralize AREG worsens LPS‐induced ALI, whereas administration of exogenous AREG ameliorates lung injury (Xu et al. ; Ogata‐Suetsugu et al. ).…”
Section: Discussionmentioning
confidence: 99%